The adoption of Wasiyyah among urban muslims in Wilayah Persekutuan Kuala Lumpur / Nurliyana Jamaluddin - Jamaluddin, Nurliyana (Faculty of Business and Management, 2018)
The issue of unclaimed and frozen assets in Malaysia is still left idle and unproductive. The frozen assets occurred are because Malaysian muslims hold a perception that the function of Islamic estate planning only comes into play when there is an intention and planning to make Wasiyyah for the purpose of charity or nonheirs (Ahmad & Peyman, 2008). It seems only those who are leaving the estates and those who probably receiving the inheritance aware the importance of Islamic estate planning (ZAR Perunding Pusaka, 2004). As an addition, The Star reported that the figure of unclaimed and frozen estate rapidly increased from RM42 billion in 2011 to RM52 billion in 2012. The latest update by Deputy Minister of Natural Resources, the number of unclaimed and frozen estate still increasing as now stood at about RM60 billion. The statistics from Syariah Judiciary Department Malaysia stated RM66 billion inheritance claims are still frozen in 2013. The continuous increasing of unclaimed and frozen asset showed that the implementation of wasiyyah in Malaysia is still lag. According to Kamarudin & Alma'mum (2013), muslims in Malaysia are still lack of attentiveness in planning their properties in their life. Thus, this research is conducted to understand the adoption of Wasiyyah among urban muslims in Wilayah Persekutuan Kuala Lumpur.